America in perspective : major trends in the United States through the 1990s - Heath, Daniel; Oxford Analytica (Firm) (Boston : Houghton Mifflin, 1986)
Results of research done in the 1980s on projections of economic prospects for growth/stagnation and stability/instability into the 1990s.
Bringing America into perspective -- Part I. Society. Changes in population : the future of the American people -- Changes in life chances : the future of the American dream -- Changes in life-styles : the future of the American way of life -- Changes in religion and values : the future of the American creed -- Part II. Politics. The actors on the political scene -- Changing institutions and machinery -- Changing attitudes and ideologies -- Part III. The economy. Productivity -- Unemployment and the changing labor market -- Monetary and fiscal policies -- Part IV. Into the 1990s. Themes of the future -- View of the future : interacting themes.
Includes index.
Revised and updated report of a study commissioned in 1981 by American Express, Bristol-Myers, and Sun Oil.
Adult.
Adult
Keywords: Economic forecasting; Economic forecasting -- United States; Social prediction -- United States; United States -- Economic conditions; United States -- Economic conditions -- 1981-; United States -- Politics and government; United States -- Politics and government -- 1981-1989 -- Forecasting; United States -- Social conditions; United States -- Social conditions -- 1980-